PENERAPAN REWARD DALAM MENINGKATKAN MOTIVASI BELAJAR PAI SISWA SD ALAM MUHAMMADIYAH KEDANYANG GRESIK - Thalata Dea Merdeka; Hasan Basri (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the application of reward methods to increase student learning enthusiasm in Islamic Religious Education (PAI) lessons at Muhammadiyah Kedanyang Elementary School in Gresik. The method used was Classroom Action Research (CAR), with two cycles involving all second-grade students as research subjects. Data collection techniques included observation, interviews, and oral tests to describe changes in student motivation before and after the implementation of rewards. The results showed a significant increase in student learning motivation after the teacher consistently provided rewards, both in the form of tangible rewards such as stickers and non-tangible rewards such as praise and recognition. Students became more active, enthusiastic, and proactive in participating during the learning process, and demonstrated improved attendance and punctuality in submitting assignments. Although some challenges, such as potential dependency on rewards, were encountered, the teacher was able to overcome them by implementing the principle of reward-giving wisely and in a balanced manner. These findings demonstrate that rewards can be an effective strategy in fostering student learning motivation and positive behavior in Islamic Religious Education (PAI) subjects in elementary schools.